3D bolted cohesive element for the modelling of bolt-reinforced rough rock-shotcrete interfaces. (September 2020) - Dong, Xiangjian; Karrech, Ali; Elchalakani, Mohamed; Qi, Chongchong; Manca, Mirko
Abstract: In this paper, we develop a novel 3D computational method that describes the behaviour of rock bolts and rough rock-shotcrete interfaces as support systems. Specifically, a Finite Element model has been formulated and implemented using the user-defined element (UEL) subroutine with ABAQUS. The input parameters of the bolted cohesive model are determined experimentally. Once the location of the bolts is defined, the overall force-displacement performance of the system can be simulated. In addition, the rough interface is modelled as a combination of 'bond' and 'Coulomb-friction' laws where the cohesive stiffness reduces with degradation. To validate the model, we compared its outputs to the results of direct shear and bolt pull-out tests; a good agreement between the two approaches has been obtained. In addition, a mesh independent result is observed for the overall force-displacement response, which makes our model particularly fast and efficient. Furthermore, we conducted a parametric study by investigating the effects of number of bolts, bolt installation angle and pretension on the overall behaviour.